Digital image analysis and assisted reading of the HER2 score display reduced concordance: pitfalls in the categorisation of HER2‐low breast cancer. Issue 6 (1st March 2023) - Sode, Michael; Thagaard, Jeppe; Eriksen, Jens Ole; Laenkholm, Anne‐Vibeke
Abstract : Aims: Digital image analysis (DIA) is used increasingly as an assisting tool to evaluate biomarkers, including human epidermal growth factor receptor 2 (HER2) in invasive breast cancer (BC). DIA can assist pathologists in HER2 evaluation by presenting quantitative information about the HER2 staining in APP assisted reading (AR). Concurrently, the HER2‐low category (HER2‐1+/2+ without HER2 gene amplification) has gained prominence due to newly developed antibody‐drug conjugates. However, major inter‐ and intraobserver variability have been observed for the entity. The present quality assurance study investigated the concordance between DIA and AR in clinical use, especially concerning the HER2‐low category. Methods and results: HER2 immunohistochemistry (IHC) in 761 tumours from 727 patients was evaluated in tissue microarray (TMA) cores by DIA (Visiopharm HER2‐CONNECT) and AR. Overall concordance between HER2‐scores were 73% ( n  = 552, weighted‐κ: 0.66), and 88% ( n  = 669, weighted‐κ: 0.70), when combining HER2‐0/1+. A total of 205 scores were discordant by one category, while four were discordant by two categories. A heterogeneous HER2 pattern was relatively common in the discordant cases and a pitfall in the categorisation of HER2‐low BC. AR more commonly reassigned a lower HER2 score (from HER2‐1+ to HER2‐0) within the HER2‐low subgroup ( n  = 624) compared with DIA. Conclusion: DIA and AR display moderate agreement with heterogeneous and aberrant staining, representing a source of discordance and a pitfall in the evaluation of HER2. Abstract : HER2‐low breast cancer represents an increasingly important diagnostic category. This study showed good concordance between digital image analysis (DIA) and assisted reading (AR). The article describes pitfalls in discordant cases including heterogeneous staining and aberrant staining artefacts.